2012
DOI: 10.1021/ja2115635
|View full text |Cite
|
Sign up to set email alerts
|

“Zeoball” [Sn36Ge24Se132]24–: A Molecular Anion with Zeolite-Related Composition and Spherical Shape

Abstract: Ionothermal reactions of [Ge(4)Se(10)](4-) with SnCl(4)·5H(2)O yielded [BMMIm](24)[Sn(36)Ge(24)Se(132)] (ZBT-1) and [BMIm](24)[Sn(32.5)Ge(27.5)Se(132)] [ZBT-2; B(M)MIm = 1-butyl-(2,)3-(di)methylimidazolium]. These contain the largest known discrete polyanion consisting only of main-group elements. In spite of a zeolite-related composition, the 192-atom "zeoball" anion adopts a spherical shape, which has been unprecedented in the chemistry of zeolites and their homologues and relatives. Preliminary studies indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 35 publications
1
97
0
7
Order By: Relevance
“…For instance, research from our own and Dehnen's groups showed that a combination of ILs and an organic amine as auxiliary solvent was an efficient system for the fabrication of selenidostannates, in which the organic amine and the IL cations might co-induce specific structures. 24,25 Similar phenomena have been observed in the ionothermal syntheses of zeolites; [26][27][28][29] for example, a new open-framework aluminophosphate with a unique Al/P ratio was synthesized by using an amine and ILs as co-templates. 26, 29 Thus we realize that syntheses in ILs with different SDAs would produce highly novel structures due to the chemical and compositional flexibility of SDAs.…”
Section: Introductionsupporting
confidence: 60%
“…For instance, research from our own and Dehnen's groups showed that a combination of ILs and an organic amine as auxiliary solvent was an efficient system for the fabrication of selenidostannates, in which the organic amine and the IL cations might co-induce specific structures. 24,25 Similar phenomena have been observed in the ionothermal syntheses of zeolites; [26][27][28][29] for example, a new open-framework aluminophosphate with a unique Al/P ratio was synthesized by using an amine and ILs as co-templates. 26, 29 Thus we realize that syntheses in ILs with different SDAs would produce highly novel structures due to the chemical and compositional flexibility of SDAs.…”
Section: Introductionsupporting
confidence: 60%
“…[8] Each of the eight vertices is in fact an M 3 Se 9 SBU, which is linked to the neighboring vertex through sharing SeÀSe edges,a nd such an M 3 Se 9 unit is commonly regarded as aT 2 cluster without ac orner,a so bserved in Na 2Àx Ga 2Àx Sn 1 + x Se, [19] NaBa 4 Ge 3 S 10 Cl, [20] and( BMMIm) 24 [Sn 36 Ge 24 Se 132 ]. [21] In complete contrastt ot he normalT n ,P n ,o rC nclusters, [8] such as upercu- Figure S5) are comparable to the GaÀSe bond length in K 2 CuGa 3 Se 6 (2.374(1)-2.432(1) ) [22] and GeÀSe bond length in K 2 EuGeSe 5 (2.339(2)-2.408(1) ). [23] Compound 1 contains five crystallographicallyi ndependent Cs atoms (see the Supporting Information, Figure S4).…”
Section: Structure Descriptionmentioning
confidence: 91%
“…The thermals tability of 1 is about 400 8Ch igher than those of conventional supertetrahedral clusters containing organic templates, such as (C 7 H 10 N) 2 [Ga 10 S 16 (NC 7 H 9 ) 4 ]( 573 K) [26] and ZBT-1( 527 K). [21] For at ypical ion-exchange reaction shown in Figure 3, hand-picked single crystals of 1 (25 mg) were mixed with CsBr (100 mg) and KBr (37.3 mg) fluxes in as ealed silica tube under vacuum, heated to 923 Kf ollowed by ad well time of 60 h, and then cooled to 473 K( see the Supporting Information). About 15 mg of clearl ight yellow crystals of (Cs 6 Br) 2 and cation-exchanged product (Rb 6 Br) 2 Cs 5 [Ga 15 Ge 9 Se 48 ]( 6 )a s orange-yellow crystals ( Figure 3; see the Supporting Information, Ta bles S1 and S2).…”
Section: Ion-exchange Reactionsmentioning
confidence: 99%
“…In order to obtain chalcogenides with novel structures and unique properties, several synthetic methods have been developed, such as high-temperature solid-state reactions, room-temperature solution processes, hydrothermal/solvothermal methods, and recently emerged ionthermal/surfactantthermal methods [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Mild solvothermal method has been proven to be an efficient approach to prepare these materials.…”
Section: Introductionmentioning
confidence: 99%